Red quarter moon a search for family in the shadow of Stalin - Konrad, Anne. (Toronto [Ont.] : University of Toronto Press, 2012)
"Anne Konrad's Red Quarter Moon is the gripping account of her search for family members lost and disappeared within the Soviet Union. Konrad's ancestors, Mennonites, had settled the Ukrainian steppes in the late 1790s. An ethno-religious minority, they became special objects of Soviet persecution. Though her parents fled in 1929, many relatives remained in the USSR.
Konrad's search for these missing extended family members took place over twenty years and five continents - on muddy roads, lonesome steppes, and in old letters, documents, or secret police archives. Her story emerges as both haunting and inspiring, filled with dramatically different accounts from survivors now scattered across the world. She aligns the voices of her subjects chronologically against the backdrop of Soviet policy, intertwining the historical context of the Terror Years with her own personal quest. Red Quarter Moon is an enthralling journey into the past that offers a unique look at the lives of ordinary families and individuals in the USSR."--Pub. desc.
Secrets in a KGB Building -- Discovering ; Who is this women in Karaganda? ; Who we are -- Searching, 1926-1930 ; The gates of Moscow -- The Soviet State, 1930-1933 ; Gerhard is lucky ; Justina Crosses a River -- Years of Terror, 1935-1938 ; The Bread Baker ; The Agronomist ; Peter disappeared in Bashkiria ; The Preacher -- Second World War, 1939-1945 ; Isaak's family farms collectively ; Exiled to Siberia ; The German occupation ; Ostarbeiter Girls and 'Volunteers' ; Escape from Red Paradise ; Repatriated to the Fatherland, 1945-1950 -- Prisoners and Singers in Siberia, 1941-1954 -- Maria in the Trudarmiia ; Alici and the Golden A ; Missing Red Army soldier Hans -- Survivors ; Deserted Wife and Defiant Daughter Lena ; Lena's sisters: 'Religious Fanatics' ; Did Gerhard stay lucky? -- Destinations and Endings ; Elizaveta in Donbas ; The road to Memrik ; Footsteps in Ufa ; Trans-Siberian Rail to Slavgorad ; Andrei: On the Kulunda Steppe ; Was Peter a Communist? -- The NKVD Records ; In Donets'k ; Heinrich's File ; Interrogation Records in Kherson.
Includes bibliographical references and index.
Keywords: Conrad family; Braun family; Mennonites -- Soviet Union -- Biography; Mennonites -- Soviet Union -- History -- 20th century; Persecution -- Soviet Union -- History -- 20th century; HISTORY / Europe / Russia & the Former Soviet Union; BIOGRAPHY & AUTOBIOGRAPHY / Religious; RELIGION / Christianity / Denominations; Electronic books